Long-term effects of bottom trawling on large sponges in the Gulf of Alaska. (1st November 2017) - Malecha, Patrick; Heifetz, Jonathan
Abstract: Manipulative studies that characterize short-term effects of bottom trawls on seafloor habitats are numerous, but studies that examine long-term effects are rare. The long-term (13 years) effects of a single bottom trawl on large (>20 cm) erect sponges were investigated by revisiting the site of prior experimental trawling studies. In prior studies, large sponges were assessed immediately after trawling and 1 yr post-trawling. Thirteen years post-trawling, the average density of large sponges was 31.7% lower (range 1.5–53.0%) and the incidence of sponge damage (torn, necrotic, missing tissue, prone) was 58.8% higher within strip transects in trawled versus untrawled reference areas. For all sponge species combined, the mean density of large sponges was 3.19 individuals 100 m −2 in trawled areas and 4.67 individuals 100 m −2 in reference areas. The most abundant sponge species in both trawled and reference areas was Rhabdocalyptus dawsoni . Mean density of this species differed greatly between trawled (1.57 individuals 100 m −2 ) and reference areas (2.91 individuals 100 m −2 ). Thirteen years after trawling, the mean percentage of damaged sponges on strip transects was 15.3% in trawled areas and 6.3% in reference areas. The rate of damage in trawled areas was less than that observed both immediately after trawling and 1 year later. The persistence of damage (lower sponge densities and higher rates of injury in trawled areas) and the potential resultant changes to benthic communities where deepwater habitat-forming biota, such as large erect sponges, are present provide rationale for cautious management of the long term effects of bottom trawling. Highlights: Long-term effects of bottom trawling on deepwater sponges. Density of sponges lower in trawled areas. Higher rate of damage among sponges in trawled areas. Trawl damage to the sponges Rhabdocalyptus dawsoni and Mycale loveni.